Uma amarillidácea da região como material de grande valor para estudo de citologia - Alencar, Edgard (Revista Ceres, 1939)
In this article the author, writing about the necessity of organising a botany text book in Brazil, mentions the Amaryllidaceae Alsiraemeria inodora Herb., as good material for cytological studies. The plant in question has only eight pairs of chromosomes which are large enough and quite distinet in prepaired slides.